SEJARAH ISLAM MODERN DI IRAN DAN IDE PEMBAHARUAN AYATULLAH KHOMAEINI - Aili Liila; Nurlisa Nurlisa; M. Dahlan. M; Syamzan Syukur (Adisam Publisher, 2025)
This jurnal discusses the process of the development of Islam in Iran began with Caliph Umar bin Khattab in carrying out the expansion of Islamic territories. In 820 AD, small and large dynasties also emerged in various regions of Persia which took turns controlling the Persian territories. For example, the Tahiri Dynasty (820-872 AD) in Khurasan (Iran), the Samanid Dynasty (892-999 AD), Gaznawi (999-1037 AD) and Saljuk (1037-1157 AD). Then the Safavid Dynasty (1501-1732 AD) emerged through the Shiite sect movement. This dynasty made several advances, namely in the fields of politics and military, economy, agriculture, education, and art development. The Iranian Revolution was something monumental in the history of Iran. Of course, the most prominent was the major change in politics, namely the formation of a new government system called the Islamic Republic of Iran. Based on the new and independent political system, Iran then made a big leap in other fields. Including education (science and technology)